Establishment of Beauveria bassiana as a fungal endophyte in potato plants and its virulence against potato tuber moth, Phthorimaea operculella (Lepidoptera: Gelechiidae). (24th May 2022) - Zhang, Meng‐Di; Wu, Sheng‐Yong; Yan, Jun‐Jie; Reitz, Stuart; Gao, Yu‐Lin
Abstract: The potato tuber moth, Phthorimaea operculella, is the most damaging potato pest in the world and is difficult to control as the larvae are internal feeders in the foliage and tubers. Entomopathogenic fungi that colonize plants as endophytes have lethal and sublethal pathological effects on insect pests. We show that Beauveria bassiana colonizes the aerial parts of potato plants endophytically after inoculation through soil drenching. Endophytic B. bassiana persisted in potato foliage for more than 50 days postinoculation. Bioassays indicated that foliage of B. bassiana ‐inoculated potato plants were pathogenic against larvae of P. operculella . Sublethal experiments indicated that B. bassiana negatively affected the growth, development, and reproduction of P. operculella . Development experiments showed that the weight of P. operculell a pupae reared on B. bassiana ‐colonized potato plants (4.25 mg) was significantly less than that of those reared on uninoculated control plants (8.89 mg). Compared with newly eclosed larvae fed on control plants, those fed on B. bassiana ‐inoculated plants had significantly lower survivorship, with only 17.8% developing to the adult stage. Oviposition of P. operculell a females reared on B. bassiana endophytically colonized plants was significantly lower (35 eggs/female) than of those reared on uninoculated plants (115 eggs/female). This study demonstrates that endophytic B. bassiana can be a potential biological control agent for the control and management of P. operculell a. Comparing pupal weights of P. operculella reared on potato plants inoculated with the B. bassiana strain GZGY‐1‐3 and on untreated control plants, pupae from the control plants were significantly heavier than those from treated plants. Abstract :